Processing the first full azimuth OBN survey in Australia: a step change in imaging quality. Issue 1 (1st December 2019) - Chambath, Unnikrishnan; Ganivet, Vincent; Birdus, Sergey; Zhou, Joe; Delorme, Alain; Scoby-Smith, Leigh; Gregory, Ivan; Kovacevic, Matt; Williams, Tim; Walton, Chris
Summary: Ocean Bottom Node (OBN) acquisition has been widely used in oil and gas industry to provide improved reservoir imaging when compared to conventional narrow azimuth (NAZ) towed streamer data. Its full azimuth (FAZ), high fold count, high repeatability and broadband character prove to be beneficial especially in areas with complex geological structures and were a driver to record the first OBN survey in Gorgon gas field, NW Australia. These characteristics play an important role in resolving fault shadows that have hindered interpretation on previous towed streamer datasets. Furthermore, the limitations arising from a relatively sparse receiver grid in the OBN acquisition are mitigated by an advanced processing sequence. The benefit of OBN data, and the workflow effectiveness, has delivered a step change improvement in reservoir imaging results over the Gorgon gas field.